컬럼반응조 내 충진된 다공성 zeolite-slag 세라믹에 의한 산성광산배수의 처리특성 - 임수빈 (한국수처리학회지, 26(5), 2018)
The objective of this research is to investigate the removal characteristics of heavy metals and sulfate ion from acid mine drainage (AMD) in a column reactor system by spherical-type porous zeolite-slag ceramics (ZS ceramics). The hydraulic retention time (HRT) condition of 24 hours in the column reactor system was found to more efficiently treat the AMD than that of 12 hours. The increment of mixing amount of converter slag in porous ZS ceramics from 1:1(Z:S) to 1:3(Z:S) was observed to enhance the removal efficiency of Cu, Cd, Mn, and Zn by 13.4%, 32.6%, 22.0%, and 48.2%, respectively. In addition, the 1:3(Z:S) porous ZS ceramics increased the alkali-supply capacity and average cycling period of back-washing relative to 1:1(Z:S) porous ZS ceramics. The average removal efficiencies of heavy metals and sulfate ion from AMD by the 1:3(Z:S) porous ZS ceramics in the column reactor under the HRT condition of 24 hours were Al 97.2%, As 98.3%, Cd 89.9%, Cu 95.5%, Fe 99.5%, Mn 76.0%, Pb 97.5%, Zn 73.2%, and SO42- 75.9% during 71 days of operation time. The experimental results exhibited that the porous ZS ceramics in the column reactor system could function as an efficient media for the long-term treatment of heavy metals and sulfate ion from AMD. KCI Citation Count: 0